Sex diagnosis of ovine and bovine embryos by enzymatic amplification and digestion of DNA from the ZFY/ZFX locus - Bredbacka, Peter; Peippo, Jaana (Agricultural and Food Science, 1992)
A PCR-based sex determination assay for sheep and cattle embryos was developed using mouse embryos for optimizing the protocol. Samples were lysed either enzymatically or by alkaline treatment followed by enzymatic amplification of DNA from the ZFY/ZFX locus. Sex diagnosis could be done after the digestion of the amplified product by restriction endonucleases. Ovine and bovine embryos could be sexed from biopsies as small as 1-4 cells. Some embryos were split into 2-4 sections, which were amplified separately. Blind trials with such samples demonstrated that the method was highly accurate, even when embryo biopsy was done under farm conditions. The protocol involves an in-built control. This eliminates the need for autosomal control primers, which often inhibit the amplification of the Y-chromosome-specific DNA, especially when a small amount of template is used.